ANALYSIS OF ARTISTIC AESTHETIC CREATIVITY AND CHILDREN’S ART EDUCATION BASED ON THE SCIENTIFIC SOURCES - Levytska, Valentyna (Proceedings of National Aviation University (archive), 2014)
The article deals with teaching developing and nurturing after-school arts education on the process of harmoniously developed personality. The problem of the formation of a sense of beauty in the students in Ukrainian society. Emphasis is on basic research in the field of art education, the theoretical approach to the problem. Analysis of literature on the problem of artistic and aesthetic education of youth through art.